From the womb to the tree; Child-rearing practices and beliefs among the Toraja of Sulawesi - Hoppenbrouwers, Toke; Sandarupa, Stanislaus; Donzelli, Aurora (UI Scholars Hub, 2017)
This article documents beliefs about pregnancy, birth, infant, and maternal health and infant death in Toraja, Sulawesi. We interviewed 42 mothers of babies between one week and six months old, a dozen traditional and contemporary midwives, the ritual specialist to minaa Tato' Dena', a physician and two traditional healers. We performed a cursory examination of the extent to which mothers and health professionals still adhere to the beliefs of to dolo (the ancestors or the people from before). Examples of rejected beliefs are that intercourse adversely affects breast milk and that it should await the end of the recommended two-year breastfeeding interval. While modern biomedical discourse plays a role in contemporary Toraja society, ancestral beliefs still guide practices related to the well-being of mothers and babies. Rather than total assimilation of contemporary beliefs, we discerned a dynamic interaction between medical discourse, common sense practices, and aluk to dolo proscriptions.